Climate policy commitment devices [dataset] - Dengler, Sebastian; Gerlagh, Reyer; Trautmann, Stefan T.; Kuilen, Gijs van de (Universität, 2019)
We develop a dynamic resource extraction game that mimics the global multi-generation planning problem for climate change and fossil fuel extraction. We implement the game under different conditions in the laboratory. Compared to a baseline condition, we find that policy interventions that provide a costly commitment device or reduce climate threshold uncertainty reduce resource extraction. We also study two conditions to assess the underlying social preferences and the viability of ecological dictatorship. Our results suggest that climate change policies that focus on investments that lock the economy into carbon-free energy sources provide an important commitment device in the intertemporal cooperation problem.
Deposit date: 2019-01-14
Gesehen am 30.01.2019
Keywords: Forschungsdaten; Datenbank